An integrative pan-cancer analysis revealing the difference in small ring finger family of SCF E3 ubiquitin ligases - Huang, Tingting; Li, Jiwei; Liu, Xinli; Shi, Bingbing; Li, Shiqin; An, Han-Xiang (Frontiers in Immunology, 2022)
Background The SCF (Skp1-cullin-F-box proteins) complex is the largest family of E3 ubiquitin ligases that mediate multiple specific substrate proteins degradation. Two ring-finger family members RBX1/ROC1 and RBX2/RNF7/SAG are small molecular proteins necessary for ubiquitin ligation activity of the multimeric SCF complex. Accumulating evidence indicated the involvement of RBX proteins in the pathogenesis and development of cancers, but no research using pan-cancer analysis for evaluating their difference has been directed previously. Methods We investigated RBX1/2 expression patterns and the association with clinicopathological features, and survivals of cancer patients obtained from the TCGA pan-cancer data. The binding energies of RBX1/2-CUL1 complexes were preliminarily calculated by using molecular dynamics simulations. Meanwhile, we assessed their immune infiltration level across numerous databases, including TISIDB and Timer database. Results High expression levels of RBX1/2 were observed in most cancer types and correlated with poor prognosis of patients analyzed. Nonetheless, exceptions were observed: RBX2 expression in KICH was higher than normal renal tissues and played a detrimental role in KICH. The expression of RBX1 was not associated with the prognostic risk of KICH. Moreover, the combination of RBX1 and CUL1 expression is more stable than that of RBX2 and CUL1. RBX1/2 expression showed their own specific characteristics in tumor pathological stages and grades, copy number variation and immune components. Conclusions These findings not only indicated that the difference of RBX1/2 might result in varying degrees of tumor progression, but also suggested that they might serve as biomarkers for immune infiltration in cancers, shedding new light on therapeutics of cancers.